Food healthiness judgements among Brazilian and German lay adults. - Moraes, Jessica Maria Muniz; Sproesser, Gudrun; Alvarenga, Marle dos Santos (Nutrition Bulletin, 2023)
This study investigated which foods are most saliently judged as healthy and unhealthy in Brazil and Germany and the reasons for these judgements. Dietary guidelines in the two countries differ in that those in Brazil are based on a food processing classification rather than nutrient profiling, whereas dietary guidelines in Germany do not include the processing level of food. In an online study with 355 lay adults (Brazil n = 205, Germany n = 150), we explored which foods are listed as healthy and unhealthy using a free‐listing method. The main reasons for these healthiness judgements were then identified with a one or two‐word phrase and compared between countries. Saliency analysis was conducted to identify the 15 most salient healthy and unhealthy foods in each country. Principles of content analysis were used to assess the reasons why these 15 items were listed as most salient by the participants. Results showed that both Brazilians and Germans listed mostly natural or minimally processed food (e.g. fruits, vegetables, grains, fish and milk) as healthy, whereas types of convenience and fast food, sweets and other ultra‐processed foods (e.g. chocolate, soda, French fries, pizza and hamburger) were the most salient unhealthy items listed in both countries. Differences in culturally relevant items listed in each country are discussed. Further, in both countries, despite differences in their dietary guidelines, food healthiness judgements for the most salient items listed relied heavily on the nutritional content of food, reinforced the 'good/healthy' and 'bad/unhealthy' dichotomy, and were centred on benefits or harms to the body (e.g. prevention or cause of diseases and weight control). The similarity of food healthiness judgements between the two countries, together with their agreement with conventional health claims and dietary guidelines, suggest that lay Brazilian and German adults are knowledgeable about the general concepts of 'healthy' and 'unhealthy' food. Finally, these findings suggest that rather than just providing more nutritional information, policymakers and health professionals need to take into account the multiple psychosocial and environmental determinants of eating in these countries.